If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = 2(y + 3) Reorder the terms: 3 + x = 2(y + 3) Reorder the terms: 3 + x = 2(3 + y) 3 + x = (3 * 2 + y * 2) 3 + x = (6 + 2y) Solving 3 + x = 6 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 6 + -3 + 2y Combine like terms: 3 + -3 = 0 0 + x = 6 + -3 + 2y x = 6 + -3 + 2y Combine like terms: 6 + -3 = 3 x = 3 + 2y Simplifying x = 3 + 2y
| 2(x+4)-7=3x-5(x+1) | | 8x+30y+75x+16y+4x= | | (x+3)-2(3x-7)=5x-(x+3) | | -2x-6x-113=55 | | -4.6x=-92 | | 2x^2-2x=-1 | | 4.4x+2=3.4x | | -20=4x+3(2x-2) | | 3x+4y+10+12x+y+1= | | 1x+4y=4 | | 4=2x^3+x^2-8x | | x(1+y)=a | | 20+6x(4-2)= | | 4(x+2)=6 | | 4x+5-2x=14 | | -16f-30= | | 7x-19=6x | | -9x-2x-141=68 | | -6=3(x+2) | | -17=-2+13-8n | | 5x+5y+x+8y= | | b+(-14)=15 | | 11=7+v/5 | | -3(3x-15)-(10+x)=35 | | g-3.5=-6.2 | | 16x=1-6x | | a=5.0(a+b)h | | 5(-2)-3(-3)= | | 5/6(12p+4)=-13p+4 | | x^2+(y+3)x+4y=0 | | 4x+9y=35 | | 4.5x=32 |